ERK2-regulated TIMP1 Induces Hyperproliferation of K-Ras(G12D)-Transformed Pancreatic Ductal Cells - Botta, Gregory P (Neoplasia Press Inc., 2013)
Pancreatic ductal adenocarcinoma (PDAC) commonly contains a mutation in K-Ras(G12D) and is characterized by a desmoplastic reaction composed of deregulated, proliferating cells embedded in an abnormal extracellular matrix (ECM). Our previous observations imply that inhibiting the mitogen-activated protein kinase (MAPK)-extracellular signal-regulated kinase (ERK2) kinase signal pathway reverses a matrix metalloproteinase 1-specific invasive phenotype. Here, we investigated the specific genes downstream of MAPK-ERK2 responsible for the hyperproliferative abilities of human and murine primary ductal epithelial cells (PDCs) within an ECM. Compared with control, DNA synthesis and total cell proliferation was significantly increased in human PDCs harboring the PDAC common p53, Rb/p16(INK4a), and K-Ras(G12D) mutations. Both of these effects were readily reversed following small-molecule inhibition or lentiviral silencing of ERK2. Microarray analysis of PDCs in three-dimensional (3D) culture revealed a unique, MAPK-influenced gene signature downstream of K-Ras(G12D). Unbiased hierarchical analysis permitted filtration of tissue inhibitor of matrix metalloproteinase 1 (TIMP1). Pancreatic cells isolated from Pdx1-Cre; LSL-K-ras(G12D/+)-mutated mice exhibit increased TIMP1 RNA transcription compared to wild-type littermate controls. Analyses of both 3D, in vitro human K-Ras(G12D) PDCs and data mining of publicly annotated human pancreatic data sets correlatively indicate increased levels of TIMP1 RNA. While silencing TIMP1 did not significantly effect PDC proliferation, exogenous addition of human recombinant TIMP1 significantly increased proliferation but only in transformed K-Ras(G12D) PDCs in 3D. Overall, TIMP1 is an upregulated gene product and a proliferative inducer of K-Ras(G12D)-mutated PDCs through the ERK2 signaling pathway.